Long noncoding RNA TINCR is a novel regulator of human bronchial epithelial cell differentiation state. Issue 3 (1st February 2021) - Omote, Norihito; Sakamoto, Koji; Li, Qin; Schupp, Jonas C.; Adams, Taylor; Ahangari, Farida; Chioccioli, Maurizio; DeIuliis, Giuseppe; Hashimoto, Naozumi; Hasegawa, Yoshinori; Kaminski, Naftali
Abstract: Long‐noncoding RNAs (lncRNAs) have numerous biological functions controlling cell differentiation and tissue development. The knowledge about the role of lncRNAs in human lungs remains limited. Here we found the regulatory role of the terminal differentiation‐induced lncRNA (TINCR) in bronchial cell differentiation. RNA in situ hybridization revealed that TINCR was mainly expressed in bronchial epithelial cells in normal human lung. We performed RNA sequencing analysis of normal human bronchial epithelial cells (NHBECs) with or without TINCR inhibition and found the differential expression of 603 genes, which were enriched for cell adhesion and migration, wound healing, extracellular matrix organization, tissue development and differentiation. To investigate the role of TINCR in the differentiation of NHBECs, we employed air–liquid interface culture and 3D organoid formation assay. TINCR was upregulated during differentiation, loss of TINCR significantly induced an early basal‐like cell phenotype (TP63) and a ciliated cell differentiation (FOXJ1) in late phase and TINCR overexpression suppressed basal cell phenotype and the differentiation toward to ciliated cells. Critical regulators of differentiation such as SOX2 and NOTCH genes (NOTCH1, HES1, and JAG1) were significantly upregulated by TINCR inhibition and downregulated by TINCR overexpression. RNA immunoprecipitation assay revealed that TINCR was required for the direct bindings of Staufen1 protein to SOX2, HES1, and JAG1 mRNA. Loss of Staufen1 induced TP63, SOX2, NOTCH1, HES1, and JAG1 mRNA expressions, which TINCR overexpression suppressed partially. In conclusion, TINCR is a novel regular of bronchial cell differentiation, affecting downstream regulators such as SOX2 and NOTCH genes, potentially in coordination with Staufen1. Abstract : Proposed model representing that TINCR together with STAU1 controls the expression of critical regulators of bronchial cell differentiation and maintains the normal differentiation state.